DEVELOPMENT OF INTERACTIVE LEARNING MULTIMEDIA BASED ON SMART APPS CREATOR ON PROBABILITY MATERIAL - Santoso, Budi; Ratumanan, Tanwey G; Latuny, Jonny (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2024)
The mathematics learning outcomes of students in grade VIII of SMP Negeri 12 Buru during the odd mid-semester assessment in the 2022/2023 academic year were low. The use of mathematics learning media is limited and teachers rarely use interactive learning multimedia. It is deemed necessary to improve student absorption of probability material. The purpose of the research is to provide an interactive learning multimedia application based on Smart Apps Creator in improving the understanding of grade VIII students of SMP Negeri 12 Buru on the material of probability and determine the quality of the multimedia application. This research includes development research with the ASSURE model. Data collection techniques include learning outcome tests, observations, student and teacher response questionnaires, and validity and practicality assessments. Application provision includes installing the application, setting the device type, working in the workspace area, adding sections/pages, changing the background image, entering text, images, buttons, music/audio, video, animation, hotspots, and interaction to form the project into html5 and apk files. The quality of multimedia is determined by validity, practicality, and effectiveness. The validity was obtained from material and media experts with a percentage of 82.5% and 93.5%. The practicality of multimedia was obtained from mathematics teachers with a percentage of 95.0%. The effectiveness of multimedia was obtained from the average value of the learning outcomes test, student response questionnaire, and teacher response questionnaire with a value of 76.4 and a percentage of 93.6% and 100%. The resulting multimedia is valid, practical, and effective. This multimedia development can be made for other materials